Predictors of fatal outcomes among hospitalized COVID‐19 patients with pre‐existing hypertension in China. (20th May 2021) - Wang, Tao; Tang, Ruidi; Ruan, Honglian; Chen, Ruchong; Zhang, Zili; Sang, Ling; Su, Xi; Yi, Shuting; Ni, Zhengyi; Hu, Yu; Liu, Lei; Shan, Hong; et al.
Abstract: Background: Coronavirus disease 2019 (COVID‐19) is an emerging, rapidly evolving pandemic, hypertension is one of the most common co‐existing chronic conditions and a risk factor for mortality. Nearly one‐third of the adult population is hypertensive worldwide, it is urgent to identify the factors that determine the clinical course and outcomes of COVID‐19 patients with hypertension. Methods and results: 148 COVID‐19 patients with pre‐existing hypertension with clarified outcomes (discharge or deceased) from a national cohort in China were included in this study, of whom 103 were discharged and 45 died in hospital. Multivariate regression showed higher odds of in‐hospital death associated with high‐sensitivity cardiac troponin (hs‐cTn) > 28 pg/ml (hazard ratio [HR]: 3.27, 95% confidence interval [CI]: 1.55–6.91) and interleukin‐6 (IL‐6) > 7 pg/ml (HR: 3.63, 95% CI:1.54–8.55) at admission. Patients with uncontrolled blood pressure (BP) (n = 52) which were defined as systolic BP ≥140 mm Hg or diastolic BP ≥90 mm Hg for more than once (≥2 times) during hospitalization, were more likely to have ICU admission ( p = 0.037), invasive mechanical ventilation ( p = 0.028), and renal injury ( p = 0.005). A stricter BP control with the threshold of 130/80 mm Hg was associated with lower mortality. Treatment with renin‐angiotensin‐aldosterone system (RAAS) suppressors, including angiotensin‐converting enzyme (ACE) inhibitors, angiotensin II receptor blockers (ARB), and spironolactone, was associated with a lower rate of ICU admission compared to other types of anti‐hypertensive medications (8 (22.9%) vs. 25 (43.1%), p = 0.048). Conclusion: Among COVID‐19 patients with pre‐existing hypertension, elevated hs‐cTn and IL‐6 could help clinicians to identify patients with fatal outcomes at an early stage, blood pressure control is associated with better clinical outcomes, and RAAS suppressors do not increase mortality and may decrease the need for ICU admission.